Self-lubricating aluminum coating and preparation method thereof
By preparing a self-lubricating aluminum coating doped with molybdenum disulfide-silica microcapsules and zinc oxide nanorods, the problem of high wear rate of self-lubricating coatings in humid and high-temperature environments was solved, achieving a low coefficient of friction and long lifespan self-lubricating effect.
Patent Information
- Application Number
- CN202511189345.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-25
- Publication Date
- 2025-11-28
AI Technical Summary
Existing self-lubricating coatings suffer from high wear rates in humid and high-temperature environments, and the lubricant is easily lost, resulting in poor friction reduction and wear resistance, and short service life.
A self-lubricating aluminum coating was prepared by plasma spraying using molybdenum disulfide-silica microcapsules as the self-lubricating phase, zinc oxide nanorods as the reinforcing phase, and zirconium diboride nanopowder as the high-temperature reinforcing phase. The coating was then treated with silane coupling agent and tetraethyl orthosilicate to form core-shell microcapsules, which enhanced the coating’s high-temperature resistance and self-lubricating properties.
It significantly reduces the coefficient of friction and wear rate of the coating, extends its service life, improves the high-temperature durability and oxidation resistance of the coating, and enhances the hardness and toughness of the coating.
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of self-lubricating coating materials, in particular to a self-lubricating aluminum coating and a preparation method thereof. BACKGROUND
[0002] Friction and wear are one of the main reasons for material and energy loss. Lubrication is the most effective measure to reduce friction and wear. Self-lubricating coating materials with excellent friction reduction and wear resistance have become one of the hot research fields in materials. Self-lubricating coating is a kind of functional coating prepared on the substrate (such as metal, ceramic or polymer) by surface engineering technology, which can continuously reduce the friction coefficient and wear in the friction process without external lubricant (such as oil, lubricating oil) by relying on the composition or structure characteristics of the coating. This kind of coating realizes long-term lubrication of the friction interface by embedding solid lubricant or designing special surface morphology, and is suitable for high temperature, vacuum, corrosive environment and other working conditions where traditional lubrication methods fail.
[0003] At present, self-lubricating coating materials mainly include layered solid lubricant coating, soft metal lubricating coating and polymer-based lubricating coating. Layered solid lubricant coating has the characteristics of low shear strength, but layered solid material molybdenum disulfide is excellent in vacuum / dry environment, but easy to oxidize in humid environment, and hexagonal boron nitride is resistant to high temperature and humidity, but the cost is high. Although the polymer-based lubricating coating has ultra-low friction, its load capacity is poor, and the soft metal lubricating coating will form a molten lubricating film at high temperature, which is suitable for aerospace high-temperature sliding parts. It is one of the important research directions for lubrication under harsh conditions such as high temperature and high load.
[0004] Self-lubricating coating technology has developed a variety of mature systems, mainly through material compounding, structure design and process optimization to achieve long-term friction reduction and wear resistance, but the solid lubricant is continuously lost during the friction process, which cannot be regenerated, resulting in rapid consumption of lubricant and failure after lubricant consumption. High lubricant content will also lead to a decrease in coating hardness, and the wear rate of the coating in humid and high temperature environments will also increase, affecting the friction reduction and wear resistance of the self-lubricating coating material. Therefore, it is an important problem for those skilled in the art to develop a new type of self-lubricating aluminum coating, which can optimize the various properties of the self-lubricating aluminum coating, maintain low friction coefficient and excellent self-lubricating property, and prolong the service life of the self-lubricating coating. SUMMARY
[0005] Therefore, the self-lubricating aluminum coating and a preparation method thereof are provided, the self-lubricating aluminum coating uses doped molybdenum disulfide-silicon dioxide microcapsules as a self-lubricating phase, uses zinc oxide nanorods as a doped component, and uses zirconium diboride nanometer powder as a high-temperature reinforcing phase, so that the self-lubricating aluminum coating can effectively absorb a small amount of sulfur dioxide generated in the reaction, reduce the influence on the environment, realize responsive lubrication of the coating, effectively prolong the service life of the self-lubricating coating, reduce the friction coefficient, wear rate and humidity sensitivity coefficient of the coating, and improve the high-temperature durability of the coating.
[0006] In order to achieve the above-mentioned purpose, the application provides a preparation method of a self-lubricating aluminum coating, and the steps include: S1, molybdenum disulfide is pretreated by a silane coupling agent, an ethyl silicate mixed solution is added, the pH is adjusted to 9-10, water bath reaction is performed, and after high-temperature strengthening treatment, molybdenum disulfide-silicon dioxide microcapsules are obtained; S2, zinc nitrate solution and hexamethylenetetramine solution are added respectively, the pH is adjusted to 10-11, zinc oxide nanorods are obtained after high-temperature and high-pressure hydrothermal reaction, and the microcapsules, stearic acid and zirconia balls are subjected to ball milling treatment under argon protection to obtain doped microcapsules; S3, after the raw materials are pretreated, the pretreated raw materials and a dispersant solution are added into a V-type mixer respectively, mixing treatment is performed, and then sprayed powder is obtained, the pretreated substrate and the sprayed powder are used for plasma spraying on the surface of the substrate, vacuum annealing treatment is performed, and finally the self-lubricating aluminum coating is obtained.
[0007] In some embodiments of the application, step S1 includes: S1.1, molybdenum disulfide nanosheets and a surfactant are added into an organic solvent in three times with an interval of 5 min, under the conditions of a power of 300-500 W and a pulse mode of 5 s on / 2 s off, ice bath ultrasonic dispersion is performed for 20-30 min, a silane coupling agent is slowly added at a drop rate of 0.25 mL / min, 0.1M acetic acid is used to adjust the pH to 4-5, the temperature is increased to 40-60℃, and reaction is performed under nitrogen protection at a stirring speed of 200-300 rpm for 1-2 h, so that amino surface modified molybdenum disulfide is obtained; S1.2, the modified molybdenum disulfide is dispersed in an organic solvent, the tetraethyl orthosilicate mixed solution is added dropwise at a stirring speed of 200-300 rpm and a drop rate of 1 mL / min, the pH is adjusted to 9-10 by using 10% ammonia water, and the mixture is reacted in a 40-50℃ water bath for 4-6 h, then the pH is adjusted to 7 by using 1M hydrochloric acid, the mixture is centrifuged at a speed of 8000-10000 rpm for 8-10 min, and the molybdenum disulfide-silicon dioxide microcapsules are obtained after being washed with ethanol and acetone for 3 times respectively, vacuum drying at 40-50℃, and being heated to 300℃ at a speed of 5℃ / min and then heated to 800℃ at a speed of 2℃ / min under the protection of nitrogen, and being kept for 2 h.
[0008] In some embodiments of the present application, in step S1, the particle size of the molybdenum disulfide nanosheet is 200 nm, the surfactant is hexadecyl trimethyl ammonium bromide, the organic solvent is an ethanol / water mixture with a volume ratio of 4:1, the silane coupling agent is silane coupling agent KH-550, the tetraethyl orthosilicate mixed solution is a tetraethyl orthosilicate / ethanol mixture with a volume ratio of 1:1, the mass ratio of the molybdenum disulfide nanosheet to the surfactant is 3-5:1-2, the amount of the organic solvent is 60-90% of the mass of the amino surface modified molybdenum disulfide, the amount of the silane coupling agent is 0.3-0.8% of the mass of the amino surface modified molybdenum disulfide, and the amount of the tetraethyl orthosilicate mixed solution is 30-35% of the mass of the molybdenum disulfide-silicon dioxide microcapsules.
[0009] In some embodiments of the present application, step S2 comprises: S2.1, a 0.1M zinc nitrate solution and a 0.1M hexamethylenetetramine solution are mixed, and then magnetically stirred at a stirring speed of 500-600 rpm for 30-40 min, the pH is adjusted to 10-11 by using ammonia water, the mixture is heated to 120-130℃ at a rate of 3℃ / min in a high-pressure reaction kettle, and then kept for 10-12 h, and then naturally cooled to obtain zinc oxide nanorods; S2.2, the zinc oxide nanorods are vacuum dried at 70-80℃ for 2-4 h, and then added into a ball mill tank together with the molybdenum disulfide-silicon dioxide microcapsules, stearic acid and zirconia balls, argon gas is introduced for protection, the mixture is ball milled at a speed of 180-200 rpm and in a 15 min forward-reverse alternating operation mode, and then the doped molybdenum disulfide-silicon dioxide microcapsules are obtained.
[0010] In some embodiments of the present application, in step S2, the diameter of the zirconia ball is 3-5 mm, the mass ratio of the zinc nitrate solution and the hexamethylene tetramine solution is 1-3:1-2, the mass ratio of the molybdenum disulfide-silica microcapsule and the zinc oxide nanorod is 90-99:1-3, the amount of stearic acid is 0.1-0.3% of the mass of the doped molybdenum disulfide-silica microcapsule, and the amount of the zirconia ball is 5-8% of the mass of the doped molybdenum disulfide-silica microcapsule.
[0011] In some embodiments of the present application, step S3 comprises: S3.1, screen the aluminum-silicon alloy powder, immerse the powder in a 10% sodium hydroxide solution, after 4-5 min of water bath reaction at a stirring speed of 200-300 rpm and a temperature of 40-50℃, cool to room temperature, adjust the pH to 7 with 5% nitric acid, clean with ethanol under ultrasonic conditions at a frequency of 40 kHz and a power of 300 W for 3 times, each time for 10 min, and then vacuum dry at 60-80℃ for 2-3 h to obtain pretreated aluminum-silicon alloy powder; add zirconium diboride nano powder and anhydrous ethanol into a reaction container, and perform ice bath ultrasonic treatment at a power of 300-500 W and a pulse mode of 5 s on / 2 s off for 20-30 min, add an electrostatic stabilizer, and adjust the pH to 8 with 0.1 M ammonia water to obtain a zirconium diboride suspension; place the doped molybdenum disulfide-silica microcapsule in a vacuum oven, heat to 100-120℃ at a rate of 2℃ / min, and keep the temperature for 2-3 h to obtain pretreated doped molybdenum disulfide-silica microcapsule; S3.2, add the dispersant solution in the form of a spray into a V-type mixer, add the pretreated aluminum-silicon alloy powder, and premix under the protection of argon at a rotating speed of 80-100 rpm for 10-15 min, slowly add the zirconium diboride suspension, increase the rotating speed to 200-250 rpm, mix for 1-2 h, then add the pretreated doped molybdenum disulfide-silica microcapsule, and continue to mix for 1-2 h to obtain a spray powder; S3.3, place the substrate in a thermal spraying device, perform sandblasting treatment with 60-mesh white corundum, clean with acetone under ultrasonic conditions at a power of 300-500 W and a frequency of 40-50 kHz for 10-15 min, rinse with deionized water, dehydrate with anhydrous ethanol, and dry with hot air at 70-80℃ for 20-30 min, then preheat to 200-250℃, dry the spray powder in an oven at 70-80℃ for 4-5 h, perform spraying treatment on the surface of the substrate by a plasma spraying method, and then place the substrate in a tube furnace with a vacuum degree of 5×10 -3 Pa, heat to 300℃ at a rate of 5℃ / min, then heat to 400℃ at a rate of 2℃ / min and keep the temperature for 2 h, cool to 150℃ at a rate of 3℃ / min, and then cool with the furnace to obtain a self-lubricating aluminum coating.
[0012] In some embodiments of the present application, in step S3, the aluminum-silicon alloy powder is an aluminum alloy powder with a silicon content of 12% and a particle size of 45-75 μm, the zirconium diboride nano powder has a particle size of 100 nm and a purity of 99.9%, the electrostatic stabilizer is polyethyleneimine, the dispersant solution is a stearic acid / acetone mixture with a mass percentage of 1.3%, the mass ratio of the aluminum-silicon alloy powder to the sodium hydroxide solution is 1-3:8-10, the mass ratio of the zirconium diboride nano powder to the anhydrous ethanol is 1-3:5-8, the amount of the electrostatic stabilizer is 0.3-0.5% of the mass of the zirconium diboride suspension, the amount of the dispersant solution is 0.3-0.5% of the mass of the spraying powder, and the amount of the doped molybdenum disulfide-silica microcapsule is 5-8% of the mass of the spraying powder.
[0013] In some embodiments of the present application, in step S3, the process parameters of the plasma spraying method are as follows: a current of 550 A, a voltage of 65 V, a spraying power of 30-40 kW, an argon flow rate of 40-50 SLPM, a nitrogen flow rate of 10-15 SLPM, a spraying distance of 120-150 mm, argon as the powder feeding carrier gas, a powder feeding flow rate of 8-10 SLPM, and a powder feeding rate of 25-30 g / min.
[0014] The present application provides a self-lubricating aluminum coating prepared by the preparation method of the self-lubricating aluminum coating as described above, which comprises molybdenum disulfide nanosheets, a surfactant, an organic solvent, a silane coupling agent, tetraethyl orthosilicate, zinc nitrate, hexamethylenetetramine, stearic acid, zirconia balls, an aluminum-silicon alloy powder, a zirconium diboride nano powder, anhydrous ethanol, an electrostatic stabilizer, and a dispersant. The molybdenum disulfide nanosheets serve as a core lubricating component, provide solid lubrication characteristics, form a transfer film during friction, significantly reduce the friction coefficient of the coating, and endow the self-lubricating aluminum coating with high-temperature lubrication performance. The silane coupling agent introduces amino groups on the surface of the molybdenum disulfide through a hydrolysis condensation reaction, enhances the chemical bonding between the molybdenum disulfide and the silica shell, and improves the structural stability of the molybdenum disulfide-silica microcapsule. The tetraethyl orthosilicate is used to generate a silica precursor under alkaline conditions, protects the molybdenum disulfide from high-temperature oxidation, and improves the mechanical strength of the molybdenum disulfide-silica microcapsule. The zinc nitrate is used to provide a zinc ion source, hydrothermally synthesize zinc oxide nanorods, and serve as a reinforcing phase to improve the wear resistance and toughness of the self-lubricating aluminum coating. The hexamethylenetetramine is used to slowly release hydroxyl ions, regulate the growth direction of the zinc oxide crystals, promote the anisotropic growth of the zinc oxide to form a nanorod structure, and optimize the mechanical properties of the self-lubricating aluminum coating. The stearic acid is used as a lubricant and dispersant in the ball milling process to reduce the particle agglomeration during the compounding of molybdenum disulfide-silica / zinc oxide, and to ensure uniform doping of the molybdenum disulfide-silica microcapsules; The zirconia balls are used as a ball milling medium to provide mechanical shear force, realize uniform compounding of molybdenum disulfide-silica and zinc oxide nanorods, and avoid component segregation; The aluminum-silicon alloy powder is used as a coating matrix material to provide good metal ductility and thermal conductivity, and the sodium hydroxide pretreatment removes the surface oxide layer to enhance the interface bonding with the lubricating components; The zirconium diboride nano powder is used as a high-temperature reinforcing phase to significantly improve the hardness and high-temperature oxidation resistance of the self-lubricating aluminum coating.
[0015] Compared with the prior art, the present application has the following beneficial effects: The present application utilizes doped molybdenum disulfide-silica microcapsules as a self-lubricating phase, zinc oxide nanorods as a doping component, zirconium diboride nano powder as a high-temperature reinforcing phase, and aluminum-silicon alloy powder as a coating matrix material to prepare a self-lubricating aluminum coating material. The molybdenum disulfide-silica microcapsules are prepared by using a silane coupling agent, molybdenum disulfide, and tetraethyl orthosilicate. The silanol of the silane coupling agent condenses with the hydroxyl group of the molybdenum disulfide to form a covalent bond, realizing the aminofunctional modification of the molybdenum disulfide. The amino group of the molybdenum disulfide forms a hydrogen bond with the silicon hydroxyl group of the tetraethyl orthosilicate to guide the epitaxial growth of the silica along the molybdenum disulfide crystal surface, forming a microcapsule with a core-shell structure. At the same time, high-temperature strengthening treatment converts the amorphous silica into a dense crystalline state, improving the hardness and high-temperature resistance of the shell layer. The silica shell layer blocks the penetration of water and oxygen, protecting the molybdenum disulfide from high-temperature oxidation, reducing the humidity sensitivity coefficient of the coating, and improving the high-temperature oxidation resistance of the coating. The zirconium diboride generates an oxide layer at high temperatures, further blocking the diffusion of oxygen and improving the high-temperature durability of the coating. Molybdenum disulfide is used as a solid lubricant. At room temperature, frictional shear stress causes microcracks in the silica tube wall, and molybdenum disulfide is released to form a transfer film. At high temperatures, the silica tube wall softens, accelerating the release of molybdenum disulfide. At the same time, the oxidation of zirconium diboride generates a diatomic boron trioxide lubricating phase, realizing temperature-responsive lubrication of the coating, effectively prolonging the service life of the self-lubricating coating, and reducing the friction coefficient and wear rate of the coating material. The aluminum-silicon alloy powder is used as a coating matrix material to provide good ductility and avoid brittle cracking of the coating. Zirconium diboride is used as a high-hardness reinforcing phase. The reaction between zirconium diboride and the molten aluminum-silicon alloy matrix generates a reinforcing phase, pinning grain boundaries to improve strength. Nanoparticles deflect and lengthen the crack propagation path, effectively improving the impact toughness of the coating. Zinc oxide nanorods are used as a high-toughness reinforcing phase to further enhance the hardness and wear resistance of the coating while effectively absorbing trace amounts of sulfur dioxide generated during the reaction, reducing the impact on the environment. DETAILED DESCRIPTION
[0016] In order to make the objects, technical solutions and advantages of the present application clearer, the present application will be further described in detail below with reference to the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and not used to limit the present application.
[0017] The present application provides a preparation method of a self-lubricating aluminum coating, comprising the following steps: S1, silane coupling agent pretreatment of molybdenum disulfide, adding tetraethyl orthosilicate mixed solution, adjusting pH to 9-10, water bath reaction, high temperature strengthening treatment, and then obtaining molybdenum disulfide-silicon dioxide microcapsules.
[0018] Step S1 comprises: S1.1, the molybdenum disulfide nanosheet and the surfactant are added to the organic solvent in three times, each time interval is 5 min, under the condition that the power is 300-500 W and the pulse mode is 5 s on / 2 s off, the ice bath ultrasonic dispersion is carried out for 20-30 min, then the silane coupling agent is slowly added at a drop rate of 0.25 mL / min, the pH is adjusted to 4-5 by using 0.1 M acetic acid, the temperature is increased to 40-60℃, the reaction is carried out for 1-2 h under the protection of nitrogen at a stirring speed of 200-300 rpm, and then the amino surface modified molybdenum disulfide is obtained.
[0019] The molybdenum disulfide nanosheet and the surfactant are added in three times, each time interval is 5 min, which can avoid local concentration too high leading to agglomeration and ensure uniform dispersion. The pulse mode of 5 s on / 2 s off can reduce the damage of the nanosheet caused by cavitation effect, and the ice bath can prevent the ultrasonic heat from destroying the structure of molybdenum disulfide. Under the power of 300-500 W, the ultrasonic dispersion is carried out for 20-30 min, which can ensure the sufficient exfoliation and dispersion of the molybdenum disulfide nanosheet. The drop rate is controlled at about 0.25 mL / min, and slow drop can effectively avoid local pH mutation leading to silane self-polymerization. The pH of the system is adjusted to 4-5, and the acidic condition is beneficial to promote the hydrolysis of the silane coupling agent, while avoiding the formation of gel caused by the acceleration of condensation when the pH is greater than 5. The reaction temperature is controlled at 40-60℃, which can effectively accelerate the condensation reaction between the silanol of the silane coupling agent and the hydroxyl group on the surface of the molybdenum disulfide nanosheet, while avoiding the decomposition of the silane coupling agent. The protection of nitrogen can effectively prevent the oxidation of molybdenum disulfide, and the stirring speed is controlled at 200-300 rpm, which can ensure the uniform reaction of the system and avoid sedimentation. The reaction is carried out for 1-2 h under the temperature and stirring speed, which promotes the amino surface modification of molybdenum disulfide and provides active sites for the subsequent coating of tetraethyl orthosilicate.
[0020] S1.2. The modified molybdenum disulfide was dispersed in an organic solvent. Under stirring speed of 200-300 rpm, a mixture of tetraethyl orthosilicate was added dropwise at a rate of 1 mL / min. The pH was adjusted to 9-10 with 10% ammonia water. After reacting in a water bath at 40-50℃ for 4-6 h, the pH was adjusted to 7 with 1M hydrochloric acid. The mixture was centrifuged at 8000-10000 rpm for 8-10 min and washed three times each with ethanol and acetone. After vacuum drying at 40-50℃, the mixture was placed in a tube furnace and heated to 300℃ at a rate of 5℃ / min under nitrogen protection. Then, the temperature was increased to 800℃ at a rate of 2℃ / min and held for 2 h. After cooling, molybdenum disulfide-silica microcapsules were obtained.
[0021] Adding the tetraethyl orthosilicate mixture dropwise at a rate of 1 mL / min allows for control of the silica precursor concentration gradient, preventing the formation of independent silica particles or reduced reaction efficiency. Maintaining a stirring speed of 200–300 rpm ensures uniform dispersion of the reactants, preventing molybdenum disulfide sedimentation or excessively thick localized silica layers. Adjusting the system pH to 9–10, as alkaline conditions accelerate the hydrolysis and condensation of tetraethyl orthosilicate, and controlling the water bath reaction temperature at 40–50°C balances the reaction rate with silica density, avoiding both insufficient reaction rate (due to low temperature) and incomplete coating (due to low temperature) and excessive solvent evaporation (due to high temperature). A water bath reaction of 4–6 hours within this temperature and pH range ensures the formation of a complete silica shell, preventing insufficient coating thickness (due to short bath time) and poor protection, and excessive shell thickness (due to long bath time) that negatively impacts the lubricating properties of molybdenum disulfide.
[0022] Centrifugation at 8000-10000 rpm for 8-10 minutes facilitates the separation of microcapsules from unreacted silane coupling agents or byproducts. Washing three times each with ethanol and acetone removes residual ammonia, hydrochloric acid, and organic byproducts. Vacuum drying at 40-50℃ removes solvents and prevents high-temperature damage to the molybdenum disulfide structure, while nitrogen protection prevents the reaction of molybdenum disulfide with oxygen at high temperatures. A stepped heating method removes organic matter and densifies silica in stages. Heating to 300℃ at a rate of 5℃ / min slowly removes residual solvents and surfactants, preventing boiling over. Heating to 800℃ at a rate of 2℃ / min reduces thermal stress and prevents shell cracking. Holding at this temperature for 2 hours allows for complete crystallization of silica, increasing shell density.
[0023] In step S1, the molybdenum disulfide nanosheets have a particle size of 200 nm, the surfactant is hexadecyltrimethylammonium bromide, the organic solvent is an ethanol / water mixture with a volume ratio of 4:1, the silane coupling agent is silane coupling agent KH-550, the tetraethyl orthosilicate mixture is a tetraethyl orthosilicate / ethanol mixture with a volume ratio of 1:1, the mass ratio of molybdenum disulfide nanosheets to surfactant is 3~5:1~2, the amount of organic solvent is 60~90% of the mass of amino-modified molybdenum disulfide, the amount of silane coupling agent is 0.3~0.8% of the mass of amino-modified molybdenum disulfide, and the amount of tetraethyl orthosilicate mixture is 30~35% of the mass of molybdenum disulfide-silica microcapsules.
[0024] S2. Add zinc nitrate solution and hexamethylenetetramine solution respectively, adjust the pH to 10-11, and obtain zinc oxide nanorods after high temperature and high pressure hydrothermal reaction. Then, ball mill them with microcapsules, stearic acid and zirconium oxide balls under argon protection to obtain doped microcapsules.
[0025] Step S2 includes: S2.1. Mix 0.1M zinc nitrate solution and 0.1M hexamethylenetetramine solution, stir magnetically at 500-600 rpm for 30-40 min, adjust pH to 10-11 with ammonia water, place in a high-pressure reactor, heat to 120-130℃ at a rate of 3℃ / min, keep at this temperature for 10-12 h, and after natural cooling, obtain zinc oxide nanorods.
[0026] Controlling the reactant concentration at 0.1M effectively regulates the nucleation and growth rate of zinc oxide, preventing excessively rapid nucleation leading to particle formation or excessively low reaction rates resulting in reduced yield. Maintaining a stirring speed of 500–600 rpm ensures uniform mixing of the reactants, avoiding localized concentration gradients. Stirring at this speed for 30–40 min allows for sufficient pre-reaction of zinc ions with hexamethylenetetramine, forming a homogeneous precursor solution. Adjusting the system pH to 10–11 provides an alkaline environment, promoting the formation and directional growth of zinc oxide crystal nuclei. Controlling the heating rate at 3 °C / min balances reaction kinetics and crystal growth quality, while maintaining the reaction temperature at 120–130 °C under high pressure accelerates the reaction and regulates the aspect ratio of the nanorods. Holding at this heating rate and reaction temperature for 10–12 h ensures sufficient growth of the zinc oxide nanorods, achieving the target size.
[0027] S2.2 After drying the zinc oxide nanorods under vacuum at 70~80℃ for 2~4h, add them, along with molybdenum disulfide-silica microcapsules, stearic acid, and zirconium oxide balls, into a ball mill jar. Under circulating water cooling and argon protection, ball mill for 1~3h at a speed of 180~200rpm and alternating forward and reverse rotation for 15min to obtain molybdenum disulfide-silica microcapsules.
[0028] Vacuum drying at 70-80℃ removes adsorbed moisture and solvent from the surface of zinc oxide nanorods. Drying at this temperature for 2-4 hours ensures complete drying of the zinc oxide nanorods, avoiding any impact on ball milling dispersibility or increased energy consumption, which would otherwise yield no significant benefits. Circulating water cooling effectively controls the temperature of the ball mill jar, preventing localized overheating. Argon gas is introduced for protection, providing an inert atmosphere to prevent the oxidation of molybdenum disulfide and zinc oxide during ball milling. Maintaining the rotation speed at 180-200 rpm balances grinding efficiency with material damage. A 15-minute alternating forward and reverse rotation mode prevents unidirectional material deposition and improves mixing uniformity. Ball milling at this speed and mode for 1-3 hours allows for the control of the degree of composite formation and particle size between the zinc oxide nanorods and the molybdenum disulfide-silica microcapsules.
[0029] In step S2, the diameter of the zirconia spheres is 3-5 mm, the mass ratio of zinc nitrate solution to hexamethylenetetramine solution is 1-3:1-2, the mass ratio of molybdenum disulfide-silica microcapsules to zinc oxide nanorods is 90-99:1-3, the amount of stearic acid used is 0.1-0.3% of the mass of the doped molybdenum disulfide-silica microcapsules, and the amount of zirconia spheres used is 5-8% of the mass of the doped molybdenum disulfide-silica microcapsules.
[0030] S3. After the raw materials are pretreated, they are added to a V-type mixer and mixed with the dispersant solution to obtain the coating powder. The pretreated substrate and the coating powder are then sprayed onto the substrate surface using a plasma spraying method. After vacuum annealing, a self-lubricating aluminum coating is obtained.
[0031] Step S3 includes: S3.1. Sift the aluminum-silicon alloy powder, immerse the powder in a 10% sodium hydroxide solution, stir at 200-300 rpm, react in a water bath at 40-50℃ for 4-5 min, cool to room temperature, adjust pH to 7 with 5% nitric acid, and ultrasonically clean with ethanol three times for 10 min each time at 40 kHz and 300 W. After vacuum drying at 60-80℃ for 2-3 h, the pretreated aluminum-silicon alloy powder is obtained. Zirconium diboride nanoparticles and anhydrous ethanol are added to the reaction vessel respectively, and ultrasonically treated in an ice bath for 20-30 min at a power of 300-500 W and a pulse mode of 5s on / 2s off. An electrostatic stabilizer is added, and the pH is adjusted to 8 with 0.1M ammonia water to obtain a zirconium diboride suspension. Place the doped molybdenum disulfide-silica microcapsules in a vacuum oven, heat to 100-120℃ at a rate of 2℃ / min, and hold for 2-3 h to obtain the pretreated doped molybdenum disulfide-silica microcapsules.
[0032] Soaking in sodium hydroxide solution removes the alumina layer from the aluminum-silicon alloy powder, exposing the active metal surface and enhancing the interfacial adhesion during subsequent spraying. A concentration of 10% is sufficient to dissolve the alumina. Maintaining a stirring speed of 200-300 rpm ensures uniform powder contact with the alkaline solution, preventing uneven mixing due to excessive speed or damage to the powder morphology due to excessive speed. A water bath temperature of 40-50℃ accelerates the reaction, preventing slow reactions or excessive reactions in the aluminum matrix. Reacting for 4-5 minutes at this stirring speed and water bath temperature balances oxide layer removal and matrix protection, preventing incomplete cleaning due to insufficient time or damage to the aluminum-silicon alloy powder due to excessive time. Adjusting the pH of the system to 7 after alkaline washing prevents residual alkaline solution from corroding the powder or affecting subsequent processes. Using 40kHz, 300W ultrasonic conditions generates cavitation to effectively remove adsorbed impurities. Three ultrasonic cleaning cycles with ethanol effectively remove organic contaminants while ensuring thorough cleaning. Vacuum drying at 60~80℃ for 2~3 hours can effectively prevent the re-oxidation of aluminum powder surface.
[0033] Controlling the ultrasonic power between 300 and 500 W ensures sufficient cavitation energy to overcome the van der Waals forces that cause agglomeration of zirconium diboride nanoparticles. This avoids situations where too low a power results in ineffective dispersion of nano-sized zirconium diboride, while excessive power leads to particle breakage or lattice defects. Using a 5s on / 2s off pulse mode effectively balances dispersion and heat accumulation, preventing ice bath failure. An ice bath maintains a low temperature and suppresses ultrasonic heat generation. Under this ultrasonic power and pulse mode, ice bath ultrasonic treatment for 20-30 minutes ensures thorough dispersion of the nanoparticles, avoiding uneven dispersion due to too short a time and particle breakage due to too long a time. Adjusting the system pH to 8 provides a slightly alkaline environment, optimizing the adsorption of the electrostatic stabilizer. By using a heating rate of 2℃ / min to control the stability of the temperature rise and avoid damage to the microcapsule material caused by thermal stress, and by controlling the reaction temperature at 100~120℃, the physically adsorbed water and volatile impurities on the surface of the microcapsules can be completely removed, while retaining the chemically bonded components. Holding at this temperature for 2~3 hours can ensure that heat is evenly transferred to the interior of the microcapsules, achieving deep cleaning.
[0034] S3.2 Add the dispersant solution to the V-type mixer in the form of spray, add the pretreated aluminum-silicon alloy powder, and premix at a speed of 80~100 rpm for 10~15 min under the protection of argon gas. Slowly add the zirconium diboride suspension, increase the speed to 200~250 rpm, mix for 1~2 h, add the pretreated doped molybdenum disulfide-silica microcapsules, and continue mixing for 1~2 h to obtain the spray powder.
[0035] Adding the dispersant solution via spraying forms a uniform liquid film that coats the powder particles, reducing surface energy and preventing agglomeration. Argon gas protection prevents oxidation of aluminum powder and molybdenum disulfide, avoiding the formation of impurities such as alumina or molybdenum trioxide, which can affect coating adhesion strength and lubrication performance. Maintaining the rotation speed at 80-100 rpm ensures gentle mixing, preventing excessive particle collision energy at high speeds that could lead to cold welding or deformation. Premixing for 10-15 minutes at this speed is sufficient to uniformly wet the powder with the dispersant, avoiding uneven dispersion due to insufficient premixing time and the introduction of mechanical stress due to excessive premixing time. Increasing the rotation speed to 200-250 rpm provides sufficient shear force to break up zirconium diboride agglomerates, while avoiding powder breakage or equipment overheating due to excessive speed. Mixing for 1-2 hours at this speed ensures thorough dispersion of zirconium diboride, avoiding uneven distribution due to insufficient mixing time and the introduction of impurities due to excessive mixing time. After adding pretreated doped molybdenum disulfide-silica microcapsules, maintaining a rotation speed of 200~250 rpm can maintain sufficient shear force to ensure uniform distribution of microcapsules, but is below the critical breakage speed of molybdenum disulfide. Continuing to mix at this speed for 1~2 hours can ensure uniform dispersion of microcapsules without damage.
[0036] S3.3. Place the substrate in a thermal spraying device, and after sandblasting with 60-mesh white corundum, ultrasonically clean it with acetone at a power of 300-500W and a frequency of 40-50kHz for 10-15 minutes. Rinse with deionized water, dehydrate with anhydrous ethanol, and dry with hot air at 70-80℃ for 20-30 minutes. Preheat to 200-250℃ and dry the powder in a 70-80℃ oven for 4-5 hours. Then, spray the substrate surface using plasma spraying and place it under a vacuum of 5×10⁻⁶. -3 In a tube furnace of Pa, the temperature is increased to 300°C at a rate of 5°C / min, then increased to 400°C at a rate of 2°C / min and held for 2 hours. After cooling to 150°C at a rate of 3°C / min, the temperature is cooled with the furnace to obtain a self-lubricating aluminum coating.
[0037] The substrate is treated with sandblasting, which removes the oxide layer and contaminants from the substrate surface through mechanical impact, increasing surface roughness and improving the mechanical adhesion between the coating and the substrate. 60-mesh white corundum is selected, as its high hardness and sharp edges effectively clean and roughen the surface while avoiding the introduction of impurities. Acetone is then used to clean the sandblasted substrate, dissolving non-polar contaminants. The power is controlled at 300-500W, providing sufficient energy to induce cavitation and avoiding excessive power that could cause micro-damage to the substrate surface. The frequency is controlled at 40-50kHz; low-frequency ultrasonic cavitation produces larger bubbles and stronger impact, suitable for removing stubborn contaminants. Ultrasonic cleaning at this power and frequency for 10-15 minutes ensures thorough cleaning of the substrate, avoiding both insufficient time leaving contaminants and excessive time causing surface fatigue.
[0038] Using deionized water rinsing and anhydrous ethanol dehydration effectively removes water-soluble residues, replaces moisture, and allows for rapid evaporation, reducing watermarks during the drying process. Controlling the drying temperature at 70-80℃, below the boiling point of water but sufficient to accelerate ethanol evaporation, prevents high-temperature oxidation of the substrate. Hot air drying at this temperature for 20-30 minutes ensures complete dehydration, preventing moisture vaporization during spraying and resulting in coating porosity. Preheating the substrate to 200-250℃ reduces the thermal stress difference between the substrate and coating during spraying, preventing coating cracking or peeling, and is below the recrystallization temperature of aluminum, preventing substrate softening. Drying the sprayed powder effectively removes adsorbed moisture, preventing moisture vaporization during spraying that could lead to coating porosity or poor bonding. Controlling the drying temperature at 70-80℃, below the decomposition temperature of dispersants or microcapsules, prevents powder performance degradation. Drying at this temperature for 4-5 hours ensures sufficient evaporation of deep moisture, preventing incomplete drying due to insufficient time.
[0039] Plasma spraying is used to coat the substrate surface. The plasma arc melts the powder particles and sprays them onto the substrate at high speed to form a dense coating, while the vacuum degree is controlled at 5×10. -3 The extremely high vacuum reduces the risk of oxidation and prevents coating performance degradation. A stepped heating method is employed: heating to 300℃ at a rate of 5℃ / min to slowly prevent thermal shock and coating cracking; then heating to 400℃ at a rate of 2℃ / min, close to the recrystallization temperature of aluminum, with an even slower rate to homogenize the microstructure; holding at this temperature for 2 hours ensures full stress release and completion of the diffusion reaction. Cooling to 150℃ at a rate of 3℃ / min followed by furnace cooling prevents rapid cooling from introducing new stresses and further balances the microstructure during furnace cooling.
[0040] In step S3, the aluminum-silicon alloy powder is an aluminum alloy powder with a silicon content of 12% and a particle size of 45-75 μm; the zirconium diboride nanoparticles have a particle size of 100 nm and a purity of 99.9%; the electrostatic stabilizer is polyethyleneimine; the dispersant solution is a stearic acid / acetone mixture with a mass percentage of 1.3%; the mass ratio of aluminum-silicon alloy powder to sodium hydroxide solution is 1-3:8-10; the mass ratio of zirconium diboride nanoparticles to anhydrous ethanol is 1-3:5-8; the amount of electrostatic stabilizer is 0.3-0.5% of the mass of zirconium diboride suspension; the amount of dispersant solution is 0.3-0.5% of the mass of spray powder; and the amount of molybdenum disulfide-silica microcapsules is 5-8% of the mass of spray powder.
[0041] In step S3, the process parameters of the plasma spraying method are as follows: current is 550A, voltage is 65V, spraying power is 30~40kW, argon flow rate is 40~50SLPM, nitrogen flow rate is 10~15SLPM, spraying distance is 120~150mm, powder carrier gas is argon, powder flow rate is 8~10SLPM, and powder feeding rate is 25~30g / min.
[0042] This invention proposes a self-lubricating aluminum coating, prepared by the method described above, comprising molybdenum disulfide nanosheets, a surfactant, an organic solvent, a silane coupling agent, tetraethyl orthosilicate, zinc nitrate, hexamethylenetetramine, stearic acid, zirconium oxide spheres, aluminum-silicon alloy powder, zirconium diboride nanoparticles, anhydrous ethanol, an electrostatic stabilizer, and a dispersant; wherein, Molybdenum disulfide nanosheets serve as the core lubricating component, providing solid lubrication properties. During friction, they form a transfer film, significantly reducing the coating's coefficient of friction and imparting high-temperature lubrication performance to the self-lubricating aluminum coating. Silane coupling agents introduce amino groups onto the surface of molybdenum disulfide through hydrolysis and condensation reactions, thereby enhancing the chemical bonding between molybdenum disulfide and the silica shell and improving the structural stability of molybdenum disulfide-silica microcapsules. Tetraethyl orthosilicate is used to hydrolyze under alkaline conditions to generate silica precursor, which protects molybdenum disulfide from high-temperature oxidation and improves the mechanical strength of molybdenum disulfide-silica microcapsules; Zinc nitrate is used to provide a zinc ion source for the hydrothermal synthesis of zinc oxide nanorods, which serve as a reinforcing phase to improve the wear resistance and toughness of self-lubricating aluminum coatings. Hexamethylenetetramine is used to slowly release hydroxide ions, regulate the growth direction of zinc oxide crystals, promote the anisotropic growth of zinc oxide to form nanorod structures, and optimize the mechanical properties of self-lubricating aluminum coatings. Stearic acid, as a lubricant and dispersant in the ball milling process, is used to reduce particle agglomeration during molybdenum disulfide-silica / zinc oxide composites, ensuring uniform doping of molybdenum disulfide-silica microcapsules. Zirconia balls, used as milling media, provide mechanical shearing force to achieve uniform composite of molybdenum disulfide-silica and zinc oxide nanorods, avoiding component segregation. Aluminum-silicon alloy powder, as a coating matrix material, provides good metal ductility and thermal conductivity. Sodium hydroxide pretreatment removes the surface oxide layer and enhances the interfacial bonding with lubricating components. Zirconium diboride nanoparticles, as a high-temperature reinforcing phase, significantly improve the hardness and high-temperature oxidation resistance of self-lubricating aluminum coatings.
[0043] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A method for preparing a self-lubricating aluminum coating, characterized in that the steps include... include: S1. Molybdenum disulfide was pretreated with silane coupling agent, added to a mixture of tetraethyl orthosilicate, the pH was adjusted to 9-10, and a water bath reaction was carried out. After high-temperature intensification treatment, molybdenum disulfide-silica microcapsules were obtained. S2. Add zinc nitrate solution and hexamethylenetetramine solution respectively, adjust the pH to 10-11, and obtain zinc oxide nanorods after high temperature and high pressure hydrothermal reaction. Then, ball mill them with microcapsules, stearic acid and zirconium oxide balls under argon protection to obtain doped microcapsules. S3. After the raw materials are pretreated, they are added to a V-type mixer and mixed with the dispersant solution to obtain the coating powder. The pretreated substrate and the coating powder are then sprayed onto the substrate surface using a plasma spraying method. After vacuum annealing, a self-lubricating aluminum coating is obtained.
2. The method for preparing a self-lubricating aluminum coating according to claim 1, characterized in that, Step S1 includes: S1.
1. Molybdenum disulfide nanosheets and surfactants were added to an organic solvent in three portions, with a 5-minute interval between each addition. The mixture was ultrasonically dispersed in an ice bath at a power of 300-500W and a pulse mode with 5s on and 2s off. Then, silane coupling agent was slowly added dropwise at a rate of 0.25 mL / min. The pH was adjusted to 4-5 with 0.1M acetic acid. The temperature was raised to 40-60℃ and the mixture was stirred at 200-300 rpm for 1-2 hours under nitrogen protection to obtain amino-modified molybdenum disulfide. S1.
2. The modified molybdenum disulfide was dispersed in an organic solvent. Under stirring speed of 200-300 rpm, a mixture of tetraethyl orthosilicate was added dropwise at a rate of 1 mL / min. The pH was adjusted to 9-10 with 10% ammonia. After reacting in a water bath at 40-50℃ for 4-6 h, the pH was adjusted to 7 with 1M hydrochloric acid. After high-speed centrifugation, washing, and vacuum drying, the mixture was placed in a tube furnace and heated to 300℃ at a rate of 5℃ / min under nitrogen protection. Then, the temperature was increased to 800℃ at a rate of 2℃ / min and held for 2 h. After cooling, molybdenum disulfide-silica microcapsules were obtained.
3. The method for preparing a self-lubricating aluminum coating according to claim 2, characterized in that, In step S1, the molybdenum disulfide nanosheets have a particle size of 200 nm; the surfactant is hexadecyltrimethylammonium bromide; the organic solvent is an ethanol / water mixture with a volume ratio of 4:1; the silane coupling agent is silane coupling agent KH-550; the tetraethyl orthosilicate mixture is a tetraethyl orthosilicate / ethanol mixture with a volume ratio of 1:1; the mass ratio of the molybdenum disulfide nanosheets to the surfactant is 3~5:1~2; the amount of the organic solvent is 60~90% of the mass of the amino-modified molybdenum disulfide; the amount of the silane coupling agent is 0.3~0.8% of the mass of the amino-modified molybdenum disulfide; and the amount of the tetraethyl orthosilicate mixture is 30~35% of the mass of the molybdenum disulfide-silica microcapsules.
4. The method for preparing a self-lubricating aluminum coating according to claim 1, characterized in that, Step S2 includes: S2.
1. Mix 0.1M zinc nitrate solution and 0.1M hexamethylenetetramine solution, stir magnetically at 500-600 rpm for 30-40 min, adjust pH to 10-11 with ammonia water, place in a high-pressure reactor, heat to 120-130℃ at a rate of 3℃ / min, keep at this temperature for 10-12 h, and after natural cooling, obtain zinc oxide nanorods; S2.
2. Vacuum-dried zinc oxide nanorods, molybdenum disulfide-silica microcapsules, stearic acid, and zirconium oxide balls were added to a ball mill jar. Under circulating water cooling and argon protection, the mixture was ball-milled for 1-3 hours at a speed of 180-200 rpm with alternating forward and reverse rotation for 15 minutes to obtain molybdenum disulfide-silica microcapsules.
5. The method for preparing a self-lubricating aluminum coating according to claim 4, characterized in that, In step S2, the diameter of the zirconia spheres is 3-5 mm; the mass ratio of the zinc nitrate solution to the hexamethylenetetramine solution is 1-3:1-2; the mass ratio of the molybdenum disulfide-silica microcapsules to the zinc oxide nanorods is 90-99:1-3; the amount of stearic acid used is 0.1-0.3% of the mass of the molybdenum disulfide-silica microcapsules; and the amount of zirconia spheres used is 5-8% of the mass of the molybdenum disulfide-silica microcapsules.
6. The method for preparing a self-lubricating aluminum coating according to claim 1, characterized in that, Step S3 includes: S3.
1. Sift the aluminum-silicon alloy powder, immerse the powder in a 10% sodium hydroxide solution, stir at 200-300 rpm, react in a water bath at 40-50℃ for 4-5 min, cool to room temperature, adjust the pH to 7 with 5% nitric acid, and obtain pretreated aluminum-silicon alloy powder after ultrasonic cleaning and vacuum drying; add zirconium diboride nanoparticles and anhydrous ethanol to the reaction vessel respectively, and sonicate in an ice bath for 20-30 min under the conditions of 300-500W power and pulse mode of 5s on / 2s off, add an electrostatic stabilizer, and adjust the pH to 8 with 0.1M ammonia water to obtain zirconium diboride suspension; place the doped molybdenum disulfide-silica microcapsules in a vacuum oven, heat to 100-120℃ at a rate of 2℃ / min, and hold for 2-3 h to obtain pretreated doped molybdenum disulfide-silica microcapsules; S3.2 Add the dispersant solution to the V-type mixer in the form of spray, add the pretreated aluminum-silicon alloy powder, and premix at a speed of 80-100 rpm for 10-15 min under the protection of argon gas. Slowly add the zirconium diboride suspension, increase the speed to 200-250 rpm, mix for 1-2 h, add the pretreated doped molybdenum disulfide-silica microcapsules, and continue mixing for 1-2 h to obtain the spray powder. S3.
3. Place the substrate in a thermal spraying device, and after sandblasting, ultrasonic cleaning, and drying, preheat it to 200~250℃. Dry the powder in a 70~80℃ oven for 4~5 hours. Then, apply plasma spraying to the substrate surface and place it under a vacuum of 5×10⁻⁶. -3 In a tube furnace, the temperature is increased to 300°C at a rate of 5°C / min, and then increased to 400°C at a rate of 2°C / min and held for 2 hours to obtain a self-lubricating aluminum coating.
7. The method for preparing a self-lubricating aluminum coating according to claim 6, characterized in that, In step S3, the aluminum-silicon alloy powder is an aluminum alloy powder with a silicon content of 12% and a particle size of 45-75 μm; the zirconium diboride nanoparticles have a particle size of 100 nm and a purity of 99.9%; the electrostatic stabilizer is polyethyleneimine; the dispersant solution is a stearic acid / acetone mixture with a mass percentage of 1.3%; the mass ratio of the aluminum-silicon alloy powder to the sodium hydroxide solution is 1-3:8-10; the mass ratio of the zirconium diboride nanoparticles to the anhydrous ethanol is 1-3:5-8; the amount of the electrostatic stabilizer is 0.3-0.5% of the mass of the zirconium diboride suspension; the amount of the dispersant solution is 0.3-0.5% of the mass of the spray powder; and the amount of the doped molybdenum disulfide-silica microcapsules is 5-8% of the mass of the spray powder.
8. The method for preparing a self-lubricating aluminum coating according to claim 1, characterized in that, The process parameters of the plasma spraying method are as follows: current is 550A, voltage is 65V, spraying power is 30~40kW, argon flow rate is 40~50SLPM, nitrogen flow rate is 10~15SLPM, spraying distance is 120~150mm, powder carrier gas is argon, powder flow rate is 8~10SLPM, and powder feeding rate is 25~30g / min.
9. A self-lubricating aluminum coating, characterized in that, The self-lubricating aluminum coating is prepared by the method described in any one of claims 1 to 8, comprising molybdenum disulfide nanosheets, a surfactant, an organic solvent, a silane coupling agent, tetraethyl orthosilicate, zinc nitrate, hexamethylenetetramine, stearic acid, zirconium oxide spheres, aluminum-silicon alloy powder, zirconium diboride nanoparticles, anhydrous ethanol, an electrostatic stabilizer, and a dispersant; wherein... The molybdenum disulfide nanosheets serve as the core lubricating component, providing solid lubrication properties. During friction, they form a transfer film, significantly reducing the coating's coefficient of friction and imparting high-temperature lubrication performance to the self-lubricating aluminum coating. The silane coupling agent introduces amino groups onto the surface of molybdenum disulfide through a hydrolysis-condensation reaction, thereby enhancing the chemical bonding between molybdenum disulfide and the silica shell and improving the structural stability of the molybdenum disulfide-silica microcapsules. The tetraethyl orthosilicate is used to hydrolyze under alkaline conditions to generate a silica precursor, which protects molybdenum disulfide from high-temperature oxidation and improves the mechanical strength of the molybdenum disulfide-silica microcapsules. The zinc nitrate is used to provide a zinc ion source for hydrothermal synthesis of zinc oxide nanorods, which serve as a reinforcing phase to improve the wear resistance and toughness of the self-lubricating aluminum coating. The hexamethylenetetramine is used to slowly release hydroxide ions, regulate the growth direction of zinc oxide crystals, promote the anisotropic growth of zinc oxide to form nanorod structures, and optimize the mechanical properties of the self-lubricating aluminum coating. The stearic acid, as a lubricant and dispersant during the ball milling process, is used to reduce particle agglomeration during the molybdenum disulfide-silica / zinc oxide composite process, ensuring uniform doping of the molybdenum disulfide-silica microcapsules. The zirconia balls, used as the milling media, provide mechanical shearing force to achieve uniform composite of molybdenum disulfide-silica and zinc oxide nanorods, thus avoiding component segregation. The aluminum-silicon alloy powder serves as the coating matrix material, providing good metal ductility and thermal conductivity. Sodium hydroxide pretreatment removes the surface oxide layer and enhances the interfacial bonding with the lubricating components. The zirconium diboride nanoparticles, as a high-temperature reinforcing phase, significantly improve the hardness and high-temperature oxidation resistance of the self-lubricating aluminum coating.
Citation Information
Cited By
Liquid conveying pipeline capable of being shaped at will and forming method of liquid conveying pipeline
CN121316332A
Preparation method and application of high-temperature stable resin-based friction material
CN121609532A